2023
DOI: 10.1186/s12879-023-08203-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 condition and persisting symptoms in English schoolchildren: repeated surveys to March 2022

Abstract: Background Both post-COVID-19 condition (long COVID) and the presence of persisting symptoms that do not meet formal definitions of post-COVID-19-condition may adversely affect quality of life and function. However, their prevalence among children and young people in England is unclear. Methods We used data from repeated surveys in a large cohort of English schoolchildren from the COVID-19 Schools Infection Survey (SIS) for the school year 2021/22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Due to the historic nature of the surveys, research data on more recent variants will not be available for analysis. However, it is important to understand the dynamics of earlier variants as there are implications for current infections, and especially for the long-term health of CYP who are still affected by infection earlier on in the pandemic [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the historic nature of the surveys, research data on more recent variants will not be available for analysis. However, it is important to understand the dynamics of earlier variants as there are implications for current infections, and especially for the long-term health of CYP who are still affected by infection earlier on in the pandemic [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it remains crucial to understand whether those CYP with acute symptomatic infection are at higher risk of subsequent long-term health effects, referred to as long-COVID. Estimates of the percentage of CYP with long-COVID following infection range from 3–14% [ 1 , 4 , 9 , 10 ]. Previous studies have tended to only include CYP with a diagnosed/symptomatic infection, which may unavoidably bias estimates of the risk of long-COVID [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…This data was corroborated by a report from the UK, where persistent symptoms were frequently observed in English schoolchildren, regardless of their SARS-CoV-2 test results. Additionally, certain specific symptoms, such as loss of smell and taste, were more commonly reported among those with a positive test history [38]. Furthermore, specific to youths, some studies underscored that symptomatology can vary depending on the viral variant.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study that evaluated long-term outcomes in 12,424 pediatric COVID survivors, the pooled prevalence of long-term symptoms was 23.36% and declined over time to ~15% at one year [ 95 ]. A survey among British school children showed that they often reported different symptoms regardless of their SARS-CoV-2 test results; however, some symptoms, for instance loss of taste and/or smell, were more common in those with a previous infection [ 96 ].…”
Section: Long Covid In Children and Adolescentsmentioning
confidence: 99%